Chiral chelate ligands based on a neopentane framework; Introducing indenyl and fluorenyl donor groups - Vogelgesang, Joachim; Huttner, Gottfried; Kaifer, Elisabeth; Kircher, Peter; Rutsch, Peter; Cunskis, Sven (European journal of inorganic chemistry, 1999)
The neopentane‐derived functionalized oxetane O(CH2)2C(CH3)(CH2OMs), 1, reacts with indenyllithium (LiInd) or fluorenyllithium (LiFlu) to produce the derivatives O(CH2)2C(CH3)(CH2R) (R = indenyl, fluorenyl),...